Relationship of budget utility in empowerment and creativity - Silva, Thiago Bruno de Jesus; Lavarda, Carlos Eduardo Facin (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
The study aimed to analyze the relationship between the perceived utility level of budget functions in empowerment and creativity. An exploratory and quantitative research was developed, with primary data from a questionnaire applied to 100 managers in Brazilian organizations of information technology. Data were treated by Structural Equation Modeling. Thus, the perceived utility of budget functions provides employees with the belief that they are free to make choices within a certain defined space limit, which provides the support and autonomy structure necessary for empowerment and, in turn, the creativity.